Monoamine oxidase B inhibitor, selegiline, reduces (18)F-THK5351 uptake in the human brain - Ng, Kok Pin (Alzheimers Res Ther, 2017)
BACKGROUND: (18)F-THK5351 is a quinoline-derived tau imaging agent with high affinity to paired helical filaments (PHF). However, high levels of (18)F-THK5351 retention in brain regions thought to contain negligible concentrations of PHF raise questions about the interpretation of the positron emission tomography (PET) signals, particularly given previously described interactions between quinolone derivatives and monoamine oxidase B (MAO-B). Here, we tested the effects of MAO-B inhibition on (18)F-THK5351 brain uptake using PET and autoradiography. METHODS: Eight participants (five mild cognitive impairment, two Alzheimer’s disease, and one progressive supranuclear palsy) had baseline (18)F-AZD4694 and (18)F-THK5351 scans in order to quantify brain amyloid and PHF load, respectively. A second (18)F-THK5351 scan was conducted 1 week later, 1 h after a 10-mg oral dose of selegiline. Three out of eight patients also had a third (18)F-THK5351 scan 9–28 days after the selegiline administration. The primary outcome measure was standardized uptake value (SUV), calculated using tissue radioactivity concentration from 50 to 70 min after (18)F-THK5351 injection, normalizing for body weight and injected radioactivity. The SUV ratio (SUVR) was determined using the cerebellar cortex as the reference region. (18)F-THK5351 competition autoradiography studies in postmortem tissue were conducted using 150 and 500 nM selegiline. RESULTS: At baseline, (18)F-THK5351 SUVs were highest in the basal ganglia (0.64 ± 0.11) and thalamus (0.62 ± 0.14). In the post-selegiline scans, the regional SUVs were reduced on average by 36.7% to 51.8%, with the greatest reduction noted in the thalamus (51.8%) and basal ganglia (51.4%). MAO-B inhibition also reduced (18)F-THK5351 SUVs in the cerebellar cortex (41.6%). The SUVs remained reduced in the three patients imaged at 9–28 days. Tissue autoradiography confirmed the effects of MAO-B inhibition on (18)F-THK5351 uptake. CONCLUSIONS: These results indicate that the interpretation of (18)F-THK5351 PET images, with respect to tau, is confounded by the high MAO-B availability across the entire brain. In addition, the heterogeneous MAO-B availability across the cortex may limit the interpretation of (18)F-THK5351 scans using reference region methods.